Effect of repeated bouts of short-term exercise on plasma free and sulphoconjugated catecholamines in humans - Strobel, Günther; Reiß, Jens; Friedmann-Bette, Birgit; Bärtsch, Peter (European journal of applied physiology, 1998)
We tested the hypothesis that measurement of plasma catecholamine sulphate concentration after exercise reflects the overall activation of the sympathoadrenergic system during the whole period of repeated bouts of short-term exercise. A group of 11 male athletes performed two exercise tests at similar average power outputs consisting of three sets each. The tests either started with one set of three very intense sprints (95% of maximal running speed) followed by two sets of three less intense sprints (85% of maximal running speed; HLX) or vice versa (LHX). Similar mean areas under the curve of free noradrenaline (NA) during HLX and LHX [622 (SEM 13) vs 611 (SEM 14) nmol · l−1 · min) as well as similar mean heart rates [143 (SEM 9) vs 143 (SEM 8) beats · min−1] indicated comparable sympathetic activation during both exercise tests. Even so, plasma concentration of free NA was still significantly higher at the end of LHX than of HLX [35.7 (SEM 3.5) vs 22.5 (SEM 2.1) nmol · l−1, respectively], i.e. when exercise ended with the more intense set of sprints. Plasma noradrenaline sulphate (NA-S) increased with exercise intensity showing higher mean increments after the first set of HLX compared to LHX [1.83 (SEM 0.42) vs 1.18 (SEM 0.29) nmol · l−1; P < 0.05]. However, after the end of HLX and LHX, increments in plasma NA-S were similar [4.52 (SEM 0.76) vs 4.06 (SEM 0.79) nmol · l−1], suggesting that NA-S response changed in parallel with the overall activation of the sympathetic nervous system during repeated bouts of short-term exercise. The results supported the hypothesis that measurement of plasma NA-S immediately after repeated bouts of short-term exercise reflects overall activation of the sympathetic nervous system during prolonged periods of this type of exercise.
Gesehen am 23.01.2024